Evolution of primate interferon-induced transmembrane proteins (IFITMs): a story of gain and loss with a differentiation into a canonical cluster and IFITM retrogenes - Schelle, Luca; Abrantes, Joana; Baldauf, Hanna-Mari; Esteves, Pedro José (Frontiers in Microbiology, 2023)
Interferon-inducible transmembrane proteins (IFITMs) are a family of transmembrane proteins. The subgroup of immunity-related (IR-)IFITMs is involved in adaptive and innate immune responses, being especially active against viruses. Here, we suggest that IFITMs should be classified as 1) a canonical IFITM gene cluster, which is located on the same chromosome, and 2) IFITM retrogenes, with a random and unique location at different positions within the genome. Phylogenetic analyses of the canonical cluster revealed the existence of three novel groups of primate IFITMs (pIFITM) in the IR-IFITM clade: the prosimian pIFITMs(pro), the new world monkey pIFITMs(nwm) and the old world monkey pIFITMs(owm). Therefore, we propose a new nomenclature: IR-pIFITM1, IR-pIFITM2, IR-pIFITM3, IR-pIFITMnwm, IR-ppIFITMown and IR-pIFITMpro. We observed divergent evolution for pIFITM5 and pIFITM10, and evidence for concerted evolution and a mechanism of birth-and-death evolution model for the IR-pIFITMs. In contrast, the IFITMs scattered throughout the genomes possessed features of retrogenes retrotransposed by class 1 transposable This is a provisional file, not the final typeset article elements. The origin of the IFITM retrogenes correspond to more recent events. We hypothesize that the transcript of a canonical IFITM3 has been constantly retrotransposed using class 1 transposable elements resulting in the IFITM retro(pseudo)genes. The unique pattern of each species has most likely been caused by constant pseudogenization and loss of the retro(pseudo)genes. This suggests a third mechanism of evolution for the IR-IFITMs in primates, similar to the birth-and-death model of evolution, but via a transposable element mechanism, which resulted in retro(pseudo)genes.